2010
DOI: 10.1002/app.32897
|View full text |Cite
|
Sign up to set email alerts
|

Organic acids catalyzed polymerization of ε‐caprolactone: Synthesis and characterization

Abstract: Environmentally friendly organocatalytic synthesis of aliphatic polyesters was studied. The catalysis investigated is novel, and lends itself well to the potential production of valuable biodegradable products. The reactions were based on an organic acids-catalyzed ring-opening polymerization of e-caprolactone with fatty acid derivatives as the initiator and were performed in the absence of solvents. The chemical structures of the functionalized polymers were confirmed by 1 H and 13 C-NMR spectra. Polymers wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 83 publications
0
14
0
1
Order By: Relevance
“…The polymers synthesized in ILs showed bimodal melting peak (Figure ). These results indicated that the imperfect crystallization existed in the synthesized samples, probably because of the presence of cyclic macromolecules in the structure of the synthesized polymers. Furthermore, these results are well correlated with those obtained from NMR, MALDI‐TOF and SEC/MALLS studies, regarding the evidence of multiphase morphology of PCLs.…”
Section: Resultsmentioning
confidence: 89%
“…The polymers synthesized in ILs showed bimodal melting peak (Figure ). These results indicated that the imperfect crystallization existed in the synthesized samples, probably because of the presence of cyclic macromolecules in the structure of the synthesized polymers. Furthermore, these results are well correlated with those obtained from NMR, MALDI‐TOF and SEC/MALLS studies, regarding the evidence of multiphase morphology of PCLs.…”
Section: Resultsmentioning
confidence: 89%
“…However, the drug within the body cannot be released from the delivery matrix before degradation of the polymer [64]. Our previous study of linear PCL demonstrated a weight loss of 2.0% after 16 days of hydrolytic degradation [65]. In this work, the hydrophilicity and physicochemical properties of the obtained polymers were improved due to the presence of the PA-MAM dendrimer in the macromolecule.…”
Section: Drug Release From the Pamam/pcl/ibu Conjugatementioning
confidence: 66%
“…This is an essential aspect so as to avoid silica aggregation and a subsequent effect in the grafting kinetics . It should be noticed that there are several ways to describe how the grafting process covers the silica surface ; however, in this work we will use the organic weight fraction of the GN as the main parameter. This is obtained using TGA analysis, where it is possible to discern the inorganic (silica) and organic (grafted caprolactone) weight fractions.…”
Section: Methodsmentioning
confidence: 99%